Morphometric changes and imaging findings of diffuse liver disease in relation to intrahepatic hemodynamics - Ozaki , Kumi; Kozaka , Kazuto; Kosaka , Yasuo; Matsui , Osamu; Kimura , Hirohiko; Gabata , Toshifumi (Seram, 2021)
Diffuse hepatic diseases have a variety of etiologies, with each showing characteristic morphometric changes. These changes are closely related to micro- and macro-level intrahepatic hemodynamics, in addition to the specific underlying pathophysiology. Short-term disorders in intrahepatic hemodynamics caused by each pathophysiological condition are compensated for by the balance of blood perfusion systems using potential trans-sinusoidal, transversal, and transplexal routes of communication (micro-hemodynamics), while long-term alterations to the intrahepatic hemodynamics result in an increase in total hepatic vascular resistance. Blood flow disorders induced by this increased vascular resistance elicit hepatic cellular necrosis and fibrosis. These changes should be uniformly widespread throughout the whole liver. However, morphometric changes do not occur uniformly, with shrinkage or enlargement not occurring homogeneously. Against this background, several macro-intrahepatic hemodynamic effects arise, such as asymmetrical and complicating morphometric structures of the liver, intricate anatomy of portal venous flow and hepatic venous drainage, and zonal differentiation between central and peripheral zones. These hemodynamic factors and pathophysiological changes are related to characteristic morphometric changes in a complicated manner, based on the combination of selective atrophy and compensatory hypertrophy (atrophy-hypertrophy complex). These changes can be clearly depicted on CT and MR imaging.